Review of The Oxford Handbook of Nietzsche - Maryam Arab (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Nietzsche, as one of the most popular philosophers and elite thinkers that formed modern thought, has been studied from many dimensions. There are many books about him, and many scholars are still doing research on his life, works, and thoughts. The plurality of the works and the differences in the representation of Nietzsche’s image has led to doubt and confusion in the determination of Nietzsche’s position and understanding of his thought. The present study aims at introducing and evaluating a major, recent, and important work in Nietzsche field, called “The Oxford Handbook of Nietzsche”. This scientific and standard work has thirty-two essays from world-renowned scholars. Essays have been organized in six discrete sections such as biography, historical relations, principal works and fundamental issues such as values, epistemology and metaphysics, and developments of will to power. These essays contain striking and precise points that can influence our understanding of Nietzsche’s philosophy and provide us with a broad knowledge of the main elements of his philosophy, such as superman, will to power, and eternal recurrence. Therefore this paper, after an overview of the book and description of its general features, summarizes the content of each essay to arouse the audience’s interest in pursuing a thorough study.